Harnessing traditional wisdom: Factors influencing jamu adoption as an infectious disease supplement among young generation - Muhammad Almanfaluthi (BIO Web of Conferences)
Traditional remedies like jamu are increasingly recognized as a potential supplementary method for boosting infectious disease recovery. This study investigates the key factors influencing young people’s intention to use jamu. A survey of 720 respondents was conducted using Likert-scale questions to assess various dimensions of jamu adoption. The relationships between latent variables were analyzed using partial least squares path modelling. The results revealed that attitude (β = 0.12), perceived benefits (β = 0.12), health consciousness (β = 0.09), and convenience and accessibility (β = 0.16) all had significant positive impacts on the intention to use jamu, with p-values below 0.001. These findings suggest that young people are more likely to use jamu when they view it as beneficial for their health, convenient, and in line with modern wellness trends. In contrast, perceived behavioural control, knowledge, and awareness had weaker or insignificant direct effects, implying that convenience, social norms, and cultural identity may play a more substantial role in shaping intentions. The reliability and validity of the constructs were robust, ranging from 71% to 85%, with explained variance variables accounting for 76% (r² = 0.76).